2021
DOI: 10.1186/s40594-021-00272-5
|View full text |Cite
|
Sign up to set email alerts
|

Relations between perceived teacher’s autonomy support, cognitive appraisals and boredom in physics learning among lower secondary school students

Abstract: Background Boredom during learning activities has the potential of impeding attention, motivation, learning and eventually achievement. Yet, research focusing on its possible antecedents seems to have received less attention especially within the physics domain. Based on assumptions of the Control Value Theory of Achievement Emotions (CVTAE), this study aimed at examining gender differences and structural relationships between students’ reported perceived teacher autonomy support (PTAS), cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 80 publications
(165 reference statements)
1
14
0
Order By: Relevance
“…Therefore, teacher enthusiasm can play the role of value induction to enhance the value of tasks and reduce students’ CB. Similar studies have found a significant predictive role of perceived value on boredom ( Ekatushabe et al, 2021 ; Forsblom et al, 2021 ).…”
Section: Discussionsupporting
confidence: 71%
“…Therefore, teacher enthusiasm can play the role of value induction to enhance the value of tasks and reduce students’ CB. Similar studies have found a significant predictive role of perceived value on boredom ( Ekatushabe et al, 2021 ; Forsblom et al, 2021 ).…”
Section: Discussionsupporting
confidence: 71%
“… Conner and Pope (2013) found that teacher support was significantly positively related to students’ behavioral, cognitive, and emotional engagement. In addition, teacher support can also indirectly influence students’ academic engagement through increasing their positive achievement emotions and buffering their negative achievement emotions ( Ekatushabe et al, 2021 ; Sadoughi and Hejazi, 2021 ). Existing studies on teacher support were mainly conducted in general education ( Sadoughi and Hejazi, 2021 ), while limited attention is paid to its influence on students’ second language learning.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, it is found that teachers' autonomy support makes students feel more support and encouragement, which is not only conducive to the formation of a good teacher-student relationship but also promotes the deep learning style (Marshik et al, 2017). At the same time, it can also enrich students' self-efficacy (Ekatushabe, 2021). However, learning is an active process for learners (Ryan and Deci, 2000a).…”
Section: Introductionmentioning
confidence: 99%